Miniaturization of Power Dividers by Using Asymmetric CMRC Structures and QWLTs with Low-Cost Materials - Kittiwittayapong, S.; Torrungrueng, D.; Phaebua, K.; Sukpreecha, K.; Lertwiriyaprapa, T.; Janpugdee, P. (Radioengineering Society, 2024)
This paper presents the miniaturization of power dividers using asymmetric compact-microstrip-resonant-cell (CMRC) structures employing low-cost materials based on a quarter-wave-like transformer (QWLT). The proposed CMRC-based QWLT power divider is intended for operation at a frequency of 2.4 GHz, utilizing the FR-4 print circuit board (PCB) with a dielectric constant of 4.3 and a substrate thickness of 1.6 mm. The CMRC dimensions include a width of 5.32 mm and a length of 8.52 mm. It is found that a significant 50% size reduction of length is achieved compared to a conventional power divider, while maintaining an insertion loss (IL) of 3.3 dB, as well as achieving the return loss and isolation loss of 20 dB.
Keywords: Power divider; quarter-wave transformer (QWT); quarter-wave-like transformer (QWLT); compact microstrip resonant cell (CMRC)